The Phenomenon of Flight and its Metaphysical Ground in Nicomachean Ethics IX, 4 - Ivanoff-Sabogal, Christian (Revista de Filosofía, 2024)
This research aims to investigate the phenomenon of flight (φυγή, fuga) as it appears in book IX, chapter 4 of Aristotle’s Nicomachean Ethics. The main thematic purpose is to demonstrate that both its ultimate theoretical foundation, as well as its intrinsic foundation, lie in the metaphysical principle of actuality and potentiality. Based on this metaphysical principle, we show that the “self” from which the vicious person lives divided in the flight consists of the right understanding in its actuality, this being revealed as the precise correlate from which the vicious person flees. This interpretation restores the systematic relevance of flight in the context of friendship, as flight specifically reveals the “amicable” relationship that the vicious person maintains with their neighbors, whom they implicitly perceive as means-of-flight.
Keywords: division; actuality; potentiality; metaphysics; understanding